1998
DOI: 10.1046/j.1420-9101.1998.11040481.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and biogeography of the genus Tarentola (Sauria: Gekkonidae) in the Canary Islands, inferred from mitochondrial DNA sequences

Abstract: Sequences from fragments of the 12S ribosomal RNA and cytochrome b mitochondrial genes were used to analyze phylogenetic relationships among geckos of genus Tarentola from the Canary Islands. A surprisingly high level of within island differentiation was found in T. delalandii in Tenerife and T. boettgeri in Gran Canaria. Molecular differentiation between populations of T. angustimentalis on Lanzarote and Fuerteventura, and between Moroccan and Iberian Peninsula T. mauritanica, also indicate that at least two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
9
31
0
Order By: Relevance
“…Radiations which are contemporary with island formation commonly show a stepwise Ôisland colonized as it emergesÕ pattern from older to younger islands in the group. This has been observed among Hawaiian island birds (Fleischer et al, 1998) and crickets (Shaw, 1996), as well as Canary island lizards (Gonza alez et al, 1996;Thorpe et al, 1994), skinks (Brown and Pestano, 1998), geckos (Nogales et al, 1998), and beetles Juan et al, 1997Juan et al, , 1998. By contrast, several studies of radiation which post-date island formation have shown relatively rapid expansion and speciation, with a relatively short coalescence time within an archipelago.…”
Section: Discussionmentioning
confidence: 98%
“…Radiations which are contemporary with island formation commonly show a stepwise Ôisland colonized as it emergesÕ pattern from older to younger islands in the group. This has been observed among Hawaiian island birds (Fleischer et al, 1998) and crickets (Shaw, 1996), as well as Canary island lizards (Gonza alez et al, 1996;Thorpe et al, 1994), skinks (Brown and Pestano, 1998), geckos (Nogales et al, 1998), and beetles Juan et al, 1997Juan et al, , 1998. By contrast, several studies of radiation which post-date island formation have shown relatively rapid expansion and speciation, with a relatively short coalescence time within an archipelago.…”
Section: Discussionmentioning
confidence: 98%
“…1999), the yellow warbler ( Dendroica petechia ) to the West Indies archipelago (Klein & Brown 1994), warblers to Madagascar (Cibois et al . 1999), Tarentola geckos to Macaronesia (Nogales et al . 1998; Carranza et al .…”
Section: Multiple Colonization and Species Diversitymentioning
confidence: 99%
“…An ML a The 32 specimens used by Nogales et al (1998) for which sequences were downloaded from GenBank and incorporated into the present study. b Representatives of the reduced data set used for the molecular clock analysis.…”
Section: (A) Relationships Of the Main Island Assemblagesmentioning
confidence: 99%